Edukasi Kompres Hangat untuk Menurunkan Nyeri Disminore Primer pada Remaja Putri - Septi Panggabean; Chintia Amita; Silvina Cecillia Oktaviyani; Melani; Imtinan Nabilah; Siti Marliyati; Dita Prihardina Pertiwi (CV. ALIM'SPUBLISHING, 2026)
Primary dysmenorrhea is one of the reproductive health problems that adolescent girls often experience and can interfere with daily activities. Lack of knowledge about non-pharmacological treatment causes many adolescents to not be able to cope with menstrual pain independently. This community service activity aims to increase the knowledge of young women about giving warm compresses as a simple method to reduce the intensity of primary dysmenorrhea pain. The activity will be held on May 14, 2026 at PMB Veronika Sinaga, Batam City with a target of 12 young women aged 13–18 years. The implementation method is in the form of health counseling through lectures, discussions, demonstrations, and post-test evaluations. The results of the activity showed that all participants participated in the activity until it was finished, actively participated, and 100% obtained a post-test score of ≥70. The education provided increased participants' understanding of the meaning of dysmenorrhea, the benefits of warm compresses, how to use them correctly, and signs that require examination of health workers. This activity proves that health counseling is effective in increasing the knowledge of adolescent girls in handling dysmenorrhea independently. Increased knowledge is expected to encourage the appropriate application of warm compresses to reduce menstrual pain complaints and improve quality of life. Reproductive health education activities like this need to be carried out in a sustainable manner with the active role of health workers, especially midwives, in providing promotive and preventive education.